A Phase I, Randomized, Placebo-Controlled, 3-Day, Ascending-Dose Study of Gs-9451, An Ns3/4A Protease Inhibitor, in Genotype 1 Hepatitis C Patients. Issue 3 (April 2013) - Lawitz, Eric J; Hill, John M; Marbury, Thomas; DeMicco, Michael P; Delaney, William; Yang, Jenny; Moorehead, Lisa; Mathias, Anita; Mo, Hongmei; McHutchison, John G; Rodriguez-Torres, Maribel; Gordon, Stuart C
Background: GS-9451 is a novel inhibitor of the HCV NS3/4A protease and demonstrates potent in vitro suppression of HCV genotype 1 replicons. Methods: The safety, pharmacokinetics and antiviral efficacy of GS-9451 were evaluated in a Phase I study in treatment-naive, HCV genotype-1-infected patients. Patients were randomized to 3 days of once-daily dosing with placebo ( n =8) or GS-9451 60 mg ( n =8 genotype 1a), 200 mg ( n =8 genotype 1a; n =8 genotype 1b) or 400 mg ( n =9 genotype 1a). Plasma samples were collected up to and on day 14 for pharmacokinetic evaluation, serum HCV RNA quantitation and NS3 sequencing. Results: No patients interrupted or discontinued dosing because of an adverse event. The median (range) maximal HCV RNA reductions from baseline were -0.88 (-1.24– -0.64), -3.19 (-3.31– -2.94) and -3.64 (-4.08– -3.54) log10 IU/ml in genotype 1a patients receiving 60, 200 and 400 mg/day GS-9451, respectively, and -3.48 (-3.54– -3.03) log10 IU/ml in genotype 1b patients receiving GS-9451 200 mg/day. Median half-life ranged from 14 to 17 h. Day 3 mean concentration at the end of dosing interval was 5.5- and 17-fold above protein-binding adjusted mean 50% effective inhibitory concentration in 200 mg and 400 mg cohorts, respectively. No resistance mutations were detected with GS-9451 60 mg/day. In the 200 mg/day or 400 mg/day groups, predominant mutations were NS3 R155 (R155K) in genotype 1a patients and D168 (D168E, D168V and D168G) in genotype 1b patients. Conclusions: GS-9451 was well-tolerated. During 3 days of monotherapy, GS-9451 200 mg/day or 400 mg/day demonstrated potent antiviral activity in both HCV genotype 1a- and 1b-infected patients. GS-9451 is currently being evaluated in combination regimens with and without pegylated interferon-α.